2017
DOI: 10.1002/mus.25653
|View full text |Cite
|
Sign up to set email alerts
|

Common polymorphisms of chemokine (C‐X3‐C motif) receptor 1 gene modify amyotrophic lateral sclerosis outcome: A population‐based study

Abstract: We found that common variants of the CX3CR1 gene influence ALS survival. Our data provide further evidence for the role of neuroinflammation in ALS. Muscle Nerve 57: 212-216, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…This finding directly contradicts a study performed on a much smaller population of individuals, where the presence of V249I was associated with shorter survival [ 114 , 115 ]. Thus, it is obvious that larger cohorts of patients should be enrolled in studies to properly determine the effect of gene polymorphisms on ALS.…”
Section: Cx3cl1/cx3cr1 Signaling In Neurodegenerative Diseasescontrasting
confidence: 67%
“…This finding directly contradicts a study performed on a much smaller population of individuals, where the presence of V249I was associated with shorter survival [ 114 , 115 ]. Thus, it is obvious that larger cohorts of patients should be enrolled in studies to properly determine the effect of gene polymorphisms on ALS.…”
Section: Cx3cl1/cx3cr1 Signaling In Neurodegenerative Diseasescontrasting
confidence: 67%
“…There is no GWAS tag-SNP associated with the CX3CR1 (chemokine (C-X3-C motif) receptor 1) gene. Whereas, recently, it was reported that the V249I and T280M polymorphisms of the CX3CR1 gene are associated with the risk of ALS and modify phenotype in a large population-based series of ALS patients 20 . To explore the potential function of CX3CR1 in the brain, we explored CX3CR1 expression in different cell types of the central nervous system using the data from 21 .…”
Section: Resultsmentioning
confidence: 97%
“…In the mSOD1 G93A mouse model of ALS, Cx3cr1 −/− mice showed more neuronal loss than Cx3cr1 +/− or Cx3cr1 +/+ mice, indicating a gene-dosage neuroprotective effect 128 . In support of this role, the loss of function of Cx3cr1 seen with the V249I rs3732379 Cx3cr1 variant was associated with accelerated progression and reduced survival in some ALS patients 131 , but not in others 132 . In both studies, Cx3cr1 variants did not increase risk for ALS.…”
Section: Cx3cr1–fractalkinementioning
confidence: 90%